Exploring the effect of geometric coupling on friction and energy dissipation in rough contacts of elastic and viscoelastic coatings. (March 2021) - Menga, N.; Carbone, G.; Dini, D.
Abstract: We study the frictional behavior of both elastic and viscoelastic thin coatings bonded to a seemingly rigid substrate and sliding against a rough profile in the presence of Coulomb friction at the interface. The aim is to explore the effect of the coupling between the normal and tangential displacement fields arising from the finiteness of the material thickness and to quantify the contribution this can have on energy losses. We found that, due to normal–tangential coupling, asymmetric contacts and consequently additional friction are observed even for purely elastic layers, indeed associated with zero bulk energy dissipation. Furthermore, enhanced viscoelastic friction is reported in the case of viscoelastic coatings due to coupling, this time also entailing larger bulk energy dissipation. Geometric coupling also introduces additional interactions involving the larger scales normal displacements, which leads to a significant increase of the contact area, under given normal load, compared to the uncoupled contacts. These results show that, in the case of contact interfaces involving thin deformable coating bonded to significantly stiffer substrate, the effect of interfacial shear stresses on the frictional and contact behavior cannot be neglected.